Public perception in university and educational institutions about clonal forestry and forest biotechnology in Argentina and Venezuela. - Sharry, Sandra (2018)
Fil: Sharry, Sandra. Universidad Nacional de La Plata. Facultad de Ciencias Agrarias y Forestales. Laboratorio de Investigtaciones de la Madera (LIMAD); Argentina.